The constitution (73rd Amendment) Act what next? - Ranga Rao, S.P. (1995)
"Deprecating the lack of enthusiasm on the part of the State governments in implementing the 73rd Amendment Act, the author says that the absence of a clear functional jurisdiction for the Panchayats is the most important drawback of the Act. The mere threat of supersession is enough to bring the elected members round to the government viewpoint. Decentralisaion as a measure of debureaucratisation has utterly failed in the present set-up. Sounding a note of caution the author says love for local democracy and decentralisation should not make one blind to the Constitutional role of the soverign State gover[ments"
Keywords: Non-governmental organizations; Panchayat - India; India. Constitution - Amendments - 73rd